Ukuran Perusahaan Memoderasi Pengaruh Penilaian Aset Biologi dan Income Smoothing terhadap Volatilitas Laba - Lisna Lisnawati; Vinola Herawati (Akuntabilitas, 2022)
PSAK 69 effective January 1, 2016 has provided direction regarding the valuation of biological assets from historical value to Fair value which uses the basis of market prices which always fluctuate in line with the demand and supply of biological assets.The purpose of this study was to examine the effect of valuation of biological assets on earnings volatility by moderating firm size in manufacturing companies in the agricultural sector in Indonesia and Malaysia for the period 2016 to 2020. This study uses quantitative methods with secondary data sources with samples used through purposive sampling where the total data is 220 company year data. The results of this study are that Biological Asset Valuation and Income Smoothing have a positive effect on earnings volatility, then for the moderating variable Firm size cannot strengthen the effect of biological asset valuation on Earning Volatility and can strengthen the effect of Income Smoothing on Profit Volatility.